Determinação bromatológica de Pleurotus ostreatus cultivado em resíduos de diferentes cultivares de bananeira - Melo de Carvalho, Cristiane Suely; Bentolila de Aguiar, Lorena Vieira; Sales-Campos, Ceci; de Almeida Minhoni, Marli Teixeira [UNESP]; Nogueira de Andrade, Meire Cristina (Interciencia, 2012)
The objective of this work was to evaluate the nutritional composition (raw protein, ether extract, raw fiber, FDA, FDN and ash) of the POS 09/100 strain of Pleurotus ostreatus grown in three combinations of residues (pseudo-stem, leave and pseudo-stem + leaf) and four banana tree cultivars (Thap maeo, Prata ana, Pelipita and Caipira). The basidiomata harvested were submitted to dehydration in a forced ventilation stove with temperature adjusted to 40 degrees C until reaching constant weight, being then grinded in a knife mill. The method proposed by Kjeldahl (1883) was used to determine total nitrogen. The Weende method (AOAC, 1997) was employed to determine crude fiber, acid-detergent fiber (ADF) and neutral detergent fiber (NDF). According to the results obtained, crude protein, ash, ADF and NDF contents varied with the kind of residue and banana tree cultivar; the substrate prepared with leaves of banana tree (Prata Ana cultivar) yielded the highest crude protein (35.4%) and ash (6.7%) contents in the basidiomata of P. streams; the substrate prepared with pseudo-stein of banana tree (Prata Ana cultivar) provided the highest ADF (31.6%) and NDF (41.9%) contents in the basidiomata of P. ostreatus. Ether extract and crude fiber contents of P. ostreatus didn't vary in function of the treatments, with averages of 2.45 and 11.27%, respectively.
Bromatological characterization of Pleurotus ostreatus grown in different residues from different banana cultivars
Caracterización bromatológica de Pleurotus ostreatus cultivado en resíduos de diferentes cultivares de banano